Forgiveness in Judaism: from the Perspective of Yom Kippur Ritual - Krzysztof Pilarczyk (Nicolaus Copernicus University in Toruń, 2016)
The aim of the article is to present the main elements of the idea of forgiveness, which has developed over the centuries in Judaism, and link it with the ritual of Yom Kippur. The author discusses respectively: (1) the etymology of the Hebrew name of Yom Kippur, (2) points to the biblical messages on this holiday, (3) determines the time of its celebration, (4) describes the temple rituals associated with them and discusses their importance, (5) presents rabbinical tradition of the Day of Forgiveness included in the Talmudic treatise Joma and comments to it, and, especially, spirituality of a Judaism believer moulded under its influence, (6) shows the outline of the synagogue liturgy of Yom Kippur, and  interprets it (7) synthetically reconstructs on the basis of the collected material the very idea of forgiveness in Judaism during the second temple and rabbinic Judaism.